REGIONAL AND SECTORAL FACTORS OF FINANCIAL STABILITY OF ORGANIZATIONS OF THE STAVROPOL TERRITORY - Anna V. Chernyavskaya; Elena S. Nemzova (Вестник Северо-Кавказского федерального университета)
The article analyzes the effectiveness and financial stability of the enterprises as one of the main elements of the regional economy. Covers the main aspects of development of the enterprise on the basis of economic trends and cyclical, characterized the main defining priorities in the development of the industrial sector and services sphere.